PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KOMPENSASI SEBAGAI VARIABEL MODERASI - Ernawati, Agrona Brajahadi Nuswantoro, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
The aim of this study was the effect of motivation on employee performance; the influence of organizational culture on employee performance; the influence of compensation on employee performance; motivational influence on employee performance moderated by compensation; the influence of organizational culture on employee performance moderated by compensation. The population in this study were all employees of PT Janetra Sukoharjo as many as 30 people. The technique of collecting data using questionnaires. Data were analyzed using multiple linear regression analysis to test the difference between absolute and hypothesis testing performed by t test. The results of this study indicate that there is no significant effect of motivation on employee performance; there is significant influence of organizational culture on employee performance; there is no significant effect on the performance employee compensation; compensation does not moderate the effect of motivation on employee performance; compensation does not moderate the influence of organizational culture on employee performance. Companies are advised may improve with better motivate employees and maintain the organizational culture of the company. Keywords: motivation, organizational culture, compensation, employee performance